2014
DOI: 10.1039/c3cp55477e
|View full text |Cite
|
Sign up to set email alerts
|

The chemical origin and catalytic activity of coinage metals: from oxidation to dehydrogenation

Abstract: The high oxidation activity of coinage metals (Cu, Ag and Au) has been widely applied in various important reactions, such as oxidation of carbon monoxide, alkenes or alcohols. The catalytic behavior of those inert metals has mostly been attributable to their size effect, the physical effect. In the present study, the chemical effects on their high oxidation activity have been investigated. We mechanistically examine the direct and oxidative dehydrogenation (partial oxidation) reactions of ethanol to acetaldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 69 publications
(86 reference statements)
0
6
0
1
Order By: Relevance
“…The coinage metals and Au in particular are well-known for their catalytic role in promoting the oxidation and dehydrogenation of alcohols. 35,36 Therefore, we further studied the NF synthesis for other metals, including Ag and Cu, which together with Au constitute the coinage metal elements, all showing NF structures with different morphologies as detailed in the sections below (see Figure 7). In contrast, Pd and even Pt salts did not yield such structures, although Pt provides a high driving force for the process, further supporting the role of the coinage metals in surface-catalyzed redox reactions that drive the NF synthesis process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coinage metals and Au in particular are well-known for their catalytic role in promoting the oxidation and dehydrogenation of alcohols. 35,36 Therefore, we further studied the NF synthesis for other metals, including Ag and Cu, which together with Au constitute the coinage metal elements, all showing NF structures with different morphologies as detailed in the sections below (see Figure 7). In contrast, Pd and even Pt salts did not yield such structures, although Pt provides a high driving force for the process, further supporting the role of the coinage metals in surface-catalyzed redox reactions that drive the NF synthesis process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We further demonstrated the role of EtOH not only as solvent but also for promoting the redox reactions by employing several other reducing agents including glucose, phenol, and ascorbic acid, all resulted in NF structures with different morphologies while keeping similar overall dH and L dimensions (Figure S13, Supporting Information). The coinage metals and Au in particular are well-known for their catalytic role in promoting the oxidation and dehydrogenation of alcohols. , Therefore, we further studied the NF synthesis for other metals, including Ag and Cu, which together with Au constitute the coinage metal elements, all showing NF structures with different morphologies as detailed in the sections below (see Figure ). In contrast, Pd and even Pt salts did not yield such structures, although Pt provides a high driving force for the process, further supporting the role of the coinage metals in surface-catalyzed redox reactions that drive the NF synthesis process.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional Bronsted-Evans−Polanyi (BEP) correlation is used to examine the thermodynamical effect on reaction barriers. In previous studies, a good linear relationship has been identified in barrier and reaction energy for C−H, C−C, and O−H dissociation on vast metal surfaces including Co. 57,58 Whether the C−H and C−C cleavages on metal oxide states as Co 2+ and Co 3+ sites we emphases hold the BEP relation is not clear. Herein the relationship of the barrier and the reaction energy on Co 2+ and Co 3+ sites is plotted in Figure 3.…”
Section: Bond Scission In Ch 2 Cho (D-4) Species Frommentioning
confidence: 94%
“…Altın ise katalizör olarak, oksidasyon, hidrojenasyon ve diğer birçok dönüşüm için başarı ile kullanılmaktadır [7]. Bu sonuçlar ışığında, Grup 11 metalleri, oksidasyon aktivitelerinde önemli bir rol oynadığı için yakıt hücrelerindeki oksijen indirgeme reaksiyonu (ORR) için en iyi katalizörlerden biri olarak kabul edilmektedir [9][10][11]. Ayrıca, Cu-Ag-Au nanoalaşımları, yüzey ayrışmaları giderek daha fazla önem kazandığı için ve özellikleri iyi bilinen Grup 11 metallerinden oluştuğu için ilgi çekmektedirler [2,12].…”
Section: Introductionunclassified